Co-construction of sulfur vacancies and carbon confinement in V5S8/CNFs to induce an ultra-stable performance for half/full sodium-ion and potassium-ion batteries. Issue 9 (1st March 2021) - Xu, Lihong; Chen, Xiaochuan; Guo, Wenti; Zeng, Lingxing; Yang, Tao; Xiong, Peixun; Chen, Qinghua; Zhang, Jianmin; Wei, Mingdeng; Qian, Qingrong
Abstract : Sulfur defective V5 S8 /CNFs is synthesized by an electrospinning method, followed by sulfuration treatment. The obtained composite exhibits attractive capacities and ultra-stable cycling performances when using as anode materials for sodium-ion and potassium-ion batteries. Abstract : The construction of anode materials for sodium-ion batteries (SIBs) and potassium-ion batteries (PIBs) with a high energy and a long lifespan is significant and still challenging. Here, sulfur-defective vanadium sulfide/carbon fiber composites (D-V5 S8 /CNFs) are designed and fabricated by a facile electrospinning method, followed by sulfuration treatment. The unique architecture, in which V5 S8 nanoparticles are confined inside the carbon fiber, provides a short-range channel and abundant adsorption sites for ion storage. Moreover, enlarged interlayer spacings could also alleviate the volume changes, and offer small vdW interactions and ionic diffusion resistance to store more Na and K ions reversibly and simultaneously. The DFT calculations further demonstrate that sulfur defects can effectively facilitate the adsorption behavior of Na + and K + and offer low energy barriers for ion intercalation. Taking advantage of the functional integration of these merits, the D-V5 S8 /CNF anode exhibits excellent storage performance and long-term cycling stability. It reveals a high capacity of 462 mA h g −1 at a current density of 0.2 A g −1 in SIBs, while it is 350 mA h g −1 at 0.1 A g −1 in PIBs, as well as admirable long-term cycling characteristics (190 mA h g −1 /17 000 cycles/5 A g −1 for SIBs and 165 mA h g −1 /3000 cycles/1 A g −1 for PIBs). Practically, full SIBs upon pairing with a Na3 V2 (PO4 )3 cathode also exhibit superior performance.